Letermovir prophylaxis for cytomegalovirus in hematopoietic-cell transplantation - Marty, F. M.; Ljungman, Per; Chemaly, R. F.; Maertens, J.; Dadwal, S. S.; Duarte, R. F.; Haider, S.; Ullmann, A. J.; Katayama, Yuta; Brown, J.; Mullane, K. M.; Boeckh, Michael; et al. (New England Journal of Medicine, 2017)
BACKGROUND Cytomegalovirus (CMV) infection remains a common complication after allogeneic hematopoietic-cell transplantation. Letermovir is an antiviral drug that inhibits the CMV-terminase complex. METHODS In this phase 3, double-blind trial, we randomly assigned CMV-seropositive transplant recipients, 18 years of age or older, in a 2:1 ratio to receive letermovir or placebo, administered orally or intravenously, through week 14 after transplantation; randomization was stratified according to trial site and CMV disease risk. Letermovir was administered at a dose of 480 mg per day (or 240 mg per day in patients taking cyclosporine). Patients in whom clinically significant CMV infection (CMV disease or CMV viremia leading to preemptive treatment) developed discontinued the trial regimen and received anti-CMV treatment. The primary end point was the proportion of patients, among patients without detectable CMV DNA at randomization, who had clinically significant CMV infection through week 24 after transplantation. Patients who discontinued the trial or had missing end-point data at week 24 were imputed as having a primary endpoint event. Patients were followed through week 48 after transplantation. RESULTS From June 2014 to March 2016, a total of 565 patients underwent randomization and received letermovir or placebo beginning a median of 9 days after transplantation. Among 495 patients with undetectable CMV DNA at randomization, fewer patients in the letermovir group than in the placebo group had clinically significant CMV infection or were imputed as having a primary end-point event by week 24 after transplantation (122 of 325 patients [37.5%] vs. 103 of 170 [60.6%], P<0.001). The frequency and severity of adverse events were similar in the two groups overall. Vomiting was reported in 18.5% of the patients who received letermovir and in 13.5% of those who received placebo; edema in 14.5% and 9.4%, respectively; and atrial fibrillation or flutter in 4.6% and 1.0%, respectively. The rates of myelotoxic and nephrotoxic events were similar in the letermovir group and the placebo group. All-cause mortality at week 48 after transplantation was 20.9% among letermovir recipients and 25.5% among placebo recipients. CONCLUSIONS Letermovir prophylaxis resulted in a significantly lower risk of clinically significant CMV infection than placebo. Adverse events with letermovir were mainly of low grade.
CRIS-Team Scopus Importer:2023-03-23